Versatility of the Medial Femoral Condyle Flap for Extremity Reconstruction and Identification of Risk Factors for Nonunion, Delayed Time to Union, and Complications. Issue 4 (April 2018) - Kazmers, Nikolas H.; Thibaudeau, Stephanie; Gerety, Patrick; Lambi, Alex G.; Levin, Lawrence Scott
Abstract : Background: The medial femoral condyle (MFC) flap has become a popular choice for treatment of small bony defects. We aim to describe outcomes after MFC flap treatment of upper and lower extremity osseous defects and test the null hypothesis that no factors influence risks for nonunion, increased time to union, and complications. Methods: A retrospective chart review was performed on all patients undergoing MFC free vascularized bone flaps by the senior author between May 2010 and March 2016. Preoperative, intraoperative, and postoperative data were collected. Results: We identified 29 patients for inclusion (22 upper and 7 lower extremity reconstructions) treated with the MFC flap for diagnoses including long bone nonunion, avascular necrosis (AVN), or AVN with nonunion. Mean postoperative follow-up was 56 weeks. The average patient was 38 years old (range = 17–61 years) and had undergone 1.5 previous failed surgeries. Union was achieved in 86% of patients at a mean of 15.8 weeks (83% at 17.9 weeks for the scaphoid). No patient with lunate AVN progressed. There were no intraoperative flap complications or bone flap loss, but 28% underwent additional unplanned surgical procedures. We identified previous surgery as a risk factor for delayed union but did not observe significant risk factors predictive of nonunion or complications requiring unplanned reoperation. Conclusions: Extremity reconstruction using the MFC corticocancellous flap results in a high rate of union yet minimal donor morbidity for a challenging patient cohort. Previous surgery was a risk factor for increased time to union.